(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Many studies have delved into the connection between self-efficacy and language anxiety. However, the findings are somewhat inconsistent: self-efficacy has either positive, negative or no relationship at all with language anxiety. Therefore, this research aims to examine the relationship between students’ self-efficacy and language anxiety in learning speaking in EFL classroom. The subjects of this study were second-year English Department students at the University of Riau, Indonesia taking Speaking subject (N = 40). Data on their self-efficacy and language anxiety were collected through the questionnaire. The data analysis results reveal that the students have very good self-efficacy in speaking. They also show a moderate level of anxiety. However, statistical analysis reveals that there is no relationship between the two variables. Despite the limited number of participant, this finding is expected to shed a light on the contribution of self-efficacy and anxiety on learning speaking in EFL context. This finding suggests that although the self-efficacy and anxiety levels were similar with previous studies, there might be different patterns of relationship between these variables depending on the context. This implies that teachers should be aware of this before taking any measure to improve students speaking skills.